MODEL LATIHAN TEKNIK LEMPAR TANGKAP CABANG OLAHRAGA SOFTBALL PADA PEMULA - Oktariyana; Wan Ahmad Rizki Muharrami (Jurnal Penjaskesrek, 2018)
This study aims to develop and test the effectiveness of the product in the form of models exercise technique throwing get sports softball novices. The method used in this study is Research & Development by design development adopt model of Borg & Gall which includes 10 stages of development, namely: (1) Research and information collecting, (2) Planning, (3) Develop preliminary form of product, (4 ) Preliminary field testing, (5) Main product revision, (6) Main field testing, (7) Operational product revision, (8) Operational field testing, (9) Final product revision, and (10) Dissemination and implementation. Early products validated by the people of the matter and the people of the softball coach then it will be revised. The next stage of done the tests of clusters of small to the total number of the subject of the tests of six of the students senior high schools , and was conducted the tests of a large group to the total number of the subject of the tests of 32 students senior high schools , the result of the effectiveness of next with the subject of the tests of 32 people rate of senior high school students . The research results show that (1) products a model that is produced is shaped technique module throw get sports softball on a novic , (2) model products technique throw catch in the sport softball announced eligible used as a reference or used as a reference for teachers , students and exercise coach softball based on their own evaluation the expert of the material 3.8 and the softball coach 4.3 with category “very good” (3) the effectiveness of products evidenced through the improvement of the skill throw get sports softball with a vanish of aim for an average rate of the score pretest 65,46 and posttest 79,53. Abstrak Penelitian ini bertujuan untuk mengembangkan dan menguji keefektifan produk berupa model latihan teknik lempar tangkap cabang olahraga softball pada pemula. Metode yang digunakan dalam penelitian ini adalah Reserch & Development dengan desain pengembangan mengadopsi model dari Borg & Gall yang mencakup 10 tahapan pengembangan yaitu: (1) Research and information collecting, (2) Planning, (3) Develop preminary form of product, (4) Preliminary field testing, (5) Main product revision, (6) Main field testing, (7) Operational product revision, (8) Operational field testing, (9) Final product revision, dan (10) Dissemination and implementation. Produk awal divalidasi oleh ahli materi dan ahli pelatih softball kemudian dilakukan revisi. Tahap berikutnya dilakukan ujicoba kelompok kecil dengan jumlah subjek ujicoba 6 orang siswa tingkat SMA, dan dilakukan ujicoba kelompok besar dengan jumlah subjek ujicoba 32 siswa tingkat SMA, selanjutnya dilakukan uji efektifitas dengan subjek ujicoba 40 orang siswa tingkat SMA. Hasil penelitian menunjukkan bahwa (1) produk model yang dihasilkan adalah berbentuk modul teknik lempar tangkap olahraga softball pada pemula, (2) produk model teknik lempar tangkap cabang olahraga softball dinyatakan layak digunakan sebagai referensi atau rujukan bagi guru, siswa maupun pelatih olahraga softball berdasarkan hasil penilaian ahli materi 3,8 dan ahli pelatih softball 4,3 dengan kategori “sangat baik”. (3) kefektifan produk dibuktikan melalui peningkatan keterampilan lempar tangkap olahraga softball denga mecapai angka rata-rata skor pretest sebesar 65,46 dan posttest sebesar 79,53. Kata Kunci: Model latihan, Lempar tangkap, Softball